The N Terminus and C Terminus of Herpes Simplex Virus 1 ICP4 Cooperate To Activate Viral Gene Expression - Wagner, Lauren M. (American Society for Microbiology, 2012)
Infected cell polypeptide 4 (ICP4) activates transcription from most viral promoters. Two transactivation domains, one N-terminal and one C terminal, are largely responsible for the activation functions of ICP4. A mutant ICP4 molecule lacking the C-terminal activation domain (n208) efficiently activates many early genes, whereas late genes are poorly activated, and virus growth is severely impaired. The regions within the N terminus of ICP4 (amino acids 1 to 210) that contribute to activation were investigated by analysis of deletion mutants in the presence or absence of the C-terminal activation domain. The mutants were assessed for their abilities to support viral replication and to regulate gene expression. Several deletions in regions conserved in other alphaherpesviruses resulted in impaired activation and viral growth, without affecting DNA binding. The single small deletion that had the greatest effect on activation in the absence of the C terminus corresponded to a highly conserved stretch of amino acids between 81 and 96, rendering the molecule nonfunctional. However, when the C terminus was present, the same deletion had a minimal effect on activity. The amino terminus of ICP4 was predicted to be relatively disordered compared to the DNA-binding domain and the C-terminal 500 amino acids. Moreover, the amino terminus appears to be in a relatively extended conformation as determined by the hydrodynamic properties of several mutants. The data support a model where the amino terminus is an extended and possibly flexible region of the protein, allowing it to efficiently interact with multiple transcription factors at a distance from where it is bound to DNA, thereby enabling ICP4 to function as a general activator of polymerase II transcription. The C terminus of ICP4 can compensate for some of the mutations in the N terminus, suggesting that it either specifies redundant interactions or enables the amino terminus to function more efficiently.